Use and Production of Digital Information and Knowledge in Technical University Education - Co-operation of Faculty and Support Units - Kairamo, Anna-Kaarina; Pasanen, Irma (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
The rapidly changing educational landscape is of increasing importance in university teaching. Universities in Finland are responsible for research and education based on research. Traditionally information and support services related to using and producing knowledge, support research, and education has mostly been seen purely from the students´ perspective. Teaching in universities is still a hidden individual activity, and, as such, challenges the support units to reach and interact with the academic community. This paper will review the aspects influencing the use and production of digital information and knowledge in technical university education; examples illustrating the experiences will be given.